The effects of elite sports on later job success - Ralf Dewenter; Leonie Giessing (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
This paper analyses the income effect of the participation in elite sports. To quantify the average difference in the monthly net income of former elite athletes and non-athletes we estimate sample average treatment effect scores (SATT) by using covariate nearest-neighbour matching (CVM). While our treatment group consists of formerly funded top-level athletes, the control group of non-athletes is drawn from the SOEP database. Matching takes place by socio-demographic variables as well as measures of personal qualities and attitudes. On average, former athletes receive higher incomes than similar non-athletes. The income premium for former team sports and male athletes is even higher. Comparing the income of former female athletes with male non-athletes, we find that the participation in elite sports closes the gender-wage gap. Our results are robust to variations in the specification and statistically as well economically significant.
Keywords: C49; J30; L83; 330; funding of elite sports; nearest-neighbor matching; job success; gender-wage gap